Genetic profile of patients with epilepsy on first-line antiepileptic drugs and potential directions for personalized treatment. (July 2010) - Grover, Sandeep; Gourie-Devi, Mandaville; Baghel, Ruchi; Sharma, Sangeeta; Bala, Kiran; Gupta, Meena; Narayanasamy, Krishnamoorthy; Varma, Binuja; Gupta, Meenal; Kaur, Kavita; Talwar, Puneet; Kaur, Harpreet; et al.
Background: The first-line antiepileptic drugs, although affordable and effective in the control of seizures, are associated with adverse drug effects, and there is large interindividual variability in the appropriate dose at which patients respond favorably. This variability may partly be explained by functional consequences of genetic polymorphisms in the drug-metabolizing enzymes, such as the CYP450 family, microsomal epoxide hydrolase and UDP-glucuronosyltransferases, drug transporters, mainly ATP-binding cassette transporters, and drug targets, including sodium channels. The purpose of this study was to determine the allele and genotype frequencies of such genetic variants in patients with epilepsy from North India administered first-line antiepileptic drugs, such as phenobarbitone, phenytoin, carbamazepine and valproic acid, and compare them with worldwide epilepsy populations.Materials & methods: SNP screening of 19 functional variants from 12 genes in 392 patients with epilepsy was carried out, and the patients were classified with respect to the metabolizing rate of their drug-metabolizing enzymes, efflux rate of drug transporters and sensitivity of drug targets.Results: A total of 16 SNPs were found to be polymorphic, and the allelic frequencies for these SNPs were in conformance with Hardy–Weinberg equilibrium. Among all the polymorphisms studied, functional variants from genes encoding CYP2C19, EPHX1, ABCB1 and SCN1A were highly polymorphic in North Indian epilepsy patients, and might account for differential drug response to first-line antiepileptic drugs.Conclusion: Interethnic differences were elucidated for several polymorphisms that might be responsible for differential serum drug levels and optimal dose requirement for efficacious treatment.